2019
DOI: 10.1177/0022219419894563
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Grapheme–Phoneme Correspondences Using a Direct Mapping Approach for At-Risk Second Language Learners: A Randomized Controlled Trial

Abstract: Reading interventions developed to teach grapheme–phoneme correspondences (GPCs) were evaluated among L2 at-risk readers. In the direct mapping of grapheme (DMG) condition, children’s attention was explicitly drawn to the application of a graphemes taught on that day to shared reading of words in authentic text. In the control condition there was no such systematic daily linkage of the GPCs and texts. The two reading interventions were otherwise identical. Two hundred fifty-three Chinese Grade 1 and Grade 2 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…However, there is no shared position among all advocates of systematic phonics requiring that practices such as using authentic "real" books be eschewed. Indeed, it is quite possible to find many examples of studies carried out in England, Canada, New Zealand, and Hong Kong that show that highly systematic prescribed phonics instruction is more effective when integrated with real books compared to more de-contextualized phonics (Chen & Savage, 2014;Hatcher, Hulme, & Ellis, 1994;Shapiro & Solity, 2008;Tse & Nicholson, 2014;Yeung & Savage, 2020).…”
Section: What Is the Right Question?mentioning
confidence: 99%
“…However, there is no shared position among all advocates of systematic phonics requiring that practices such as using authentic "real" books be eschewed. Indeed, it is quite possible to find many examples of studies carried out in England, Canada, New Zealand, and Hong Kong that show that highly systematic prescribed phonics instruction is more effective when integrated with real books compared to more de-contextualized phonics (Chen & Savage, 2014;Hatcher, Hulme, & Ellis, 1994;Shapiro & Solity, 2008;Tse & Nicholson, 2014;Yeung & Savage, 2020).…”
Section: What Is the Right Question?mentioning
confidence: 99%
“…Evidence for this finding comes from a variety of native English-speaking countries, including the United States [ 20 ], the United Kingdom [ 21 ] and Australia [ 22 ]. Intervention studies on children with dyslexia and intellectual disability have also found that teaching graphene-phoneme correspondence is crucial in the initial stages of learning to read [ 23 , 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous training programs for NCSs have primarily focused on the typically developing population (Y. Li, 2012; Sun et al, 2015). Only a few studies have investigated special populations, including individuals with dyslexia, at‐risk readers, and individuals with learning disabilities impacting English language learning (Tam & Leung, 2019; Xiong, 2014; S. S. Yeung & Savage, 2020). Examining the difference in training effects between a typically developing population and the special population of NCSs is helpful for educators in adopting more targeted teaching.…”
Section: Additional Factors Influencing Training Efficacymentioning
confidence: 99%